Leeth Therapy (Jalaukavacharana) - A Novel Gift from Ayurveda for Treatment of Medico-Surgical Diseases (Indian Journal of Public Health Research & Development, 2020)
Background: The first description of Jalaukavacharana (leech therapy) was found in the text of Sushruta Samhita in 800 B.C. Recently, many researches proved that leech saliva have variety of bioactive compoundsinvolving anti-thrombin (hirudin, bufrudin), anti-platelet (calin), factor Xa inhibitors, antibacterial andothers property.Aim: Main aim of present article is to explore about procedures of leech therapy and research works doneover few decades on application of leech therapy in different medico-surgical diseases.Methodology: The procedure of leech therapy is documented from authors own observations and Informationof its application in different diseases was gathered from various published work of last ten years.Result:-Many clinical researches show that leech therapy is very effective in various medico-surgicaldiseases. Total eight publications were included in the final selection after systematic analysis.Conclusion: -Leech therapy or Jalaukavacharan is an ancient Ayurvedic bloodletting technique whichhaving the great potential to manage many inflammatory, ischemic and infectious diseases. Leech’s salivacontains many biologically and pharmacologically active compounds which exert effects anti-coagulant,profibrinolytic, anti-platelet, anti-inflammatory and anti-edema in the host’s body. Arthritis, venouscongestion, vascular diseases, abscess, ischemic heart disease etc. can be successfully manage by leechtherapy/.
Keywords: Jalaukavacharan, Leech therapy, Hirudin, Vidradhi, Deep vein thrombosis (DVT).